Discharge before noon: Effect on throughput and sustainability. Issue 10 (30th June 2015) - Wertheimer, Benjamin; Jacobs, Ramon E. A.; Iturrate, Eduardo; Bailey, Martha; Hochman, Katherine
<x xml:space="preserve">Abstract</x> BACKGROUND Late afternoon hospital discharges are thought to contribute to admission bottlenecks. We previously described an intervention that resulted in a statistically significant increase in the discharge before noon (DBN) rate on 2 inpatient medicine units. OBJECTIVE To evaluate (1) the effect of an increased DBN rate on the admission arrival time and the number of admissions per hour and (2) the sustainability of our DBN initiative. DESIGN Pre‐/postintervention retrospective analysis. SETTING Two acute‐care inpatient medicine units in a tertiary care, urban, academic medical center. PATIENTS: For the admission arrival time and admissions per hour analysis, all inpatients admitted to the medical units from June 1, 2011 to June 31, 2013. For the sustainability analysis, all patients discharged from July 1, 2013 to December 31, 2014. INTERVENTION A multidisciplinary intervention to increase the DBN rate. MEASUREMENTS: Date and time of arrival to all inpatient sites, and discharge date and time of all patients from 2 inpatient medicine units. RESULTS Concurrent with our increase in DBN rate, we found a statistically significant change in the median arrival time of emergency department (ED) admissions and transfers from 5 pm to 4 pm. High‐frequency admission peaks were statistically significantly reduced for ED admissions. The statistically significant increase in DBN rate is sustained at 35%. CONCLUSIONS Increasing the DBN rate correlates with admissions arriving earlier in the day and reductions in high‐frequency peaks of ED admissions. Statistically significant improvements in DBN rates are sustainable. Journal of Hospital Medicine 2015;10:664–669. © 2015 Society of Hospital Medicine